2015
DOI: 10.1016/j.enpol.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Public preferences for investments in renewable energy production and energy efficiency

Abstract: In this paper we investigate the choices citizens make when asked to express willingness to support a proposed energy policy and are then compelled to allocate the program funds to either renewable energy or energy efficiency. In a survey study based on a random sample of residents of the state of Maine, USA, we find that citizens have preferences for specific types of renewable energy but these preferences do not yield significantly different allocation of investment funds between renewable energy and energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 59 publications
(88 reference statements)
3
20
0
Order By: Relevance
“…In sum, our findings are line with prior research that finds more support for policy "carrots" like voluntary efforts [6], increased funding for renewable energy technologies [43], and increased energy efficiency standards [44] from respondents in all four states. Demographic characteristics of individuals are independently related to support for the eight policy questions, and our findings were relatively in-line with previous research.…”
Section: Discussionsupporting
confidence: 90%
“…In sum, our findings are line with prior research that finds more support for policy "carrots" like voluntary efforts [6], increased funding for renewable energy technologies [43], and increased energy efficiency standards [44] from respondents in all four states. Demographic characteristics of individuals are independently related to support for the eight policy questions, and our findings were relatively in-line with previous research.…”
Section: Discussionsupporting
confidence: 90%
“…Adapted from Goplen (2014). (Noblet, Teisl, Evans, et al, 2015). Further, individuals who saw Tidal energy in the Energy Policy Scenario were more likely to support the policy than if landbased wind had been presented (β = .648, p < .015).…”
Section: H1: Dose Effectmentioning
confidence: 96%
“…[14] have found that people with higher environmental attitudes are more likely to invest in RE project and even seem to accept financial disadvantages in return for the environmentally-friendly projects. [15], on the other hand, found that while people who perceive that climate change is happening, are more likely to support RE related policy, the belief, however, does not influence how much they are willing to allocate for RE investment.…”
Section: Drivers Affecting Investment Decision In Rementioning
confidence: 92%
“…This psychographic variables have been tested in several other studies on RE such as [14] and [15]. [14] have found that people with higher environmental attitudes are more likely to invest in RE project and even seem to accept financial disadvantages in return for the environmentally-friendly projects.…”
Section: Drivers Affecting Investment Decision In Rementioning
confidence: 99%
See 1 more Smart Citation